Cameroon : Requests for Three-Year Arrangements Under the Extended Credit Facility and the Extended Fund Facility-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report ;, 2022)
Cameroon, the largest economy in the Central African Economic and Monetary Union (CEMAC), continues to face the repercussions of the COVID-19 pandemic. Since the onset of the pandemic, the IMF's Executive Board has approved two disbursements under the Rapid Credit Facility (RCF) totaling SDR 276 million, about USD 382 million or 100 percent of Cameroon's quota. Cameroon's last arrangement under the Extended Credit Facility (ECF) ended in September 2020, without completion of the sixth and final review. The authorities have requested new arrangements from the IMF to help maintain external sustainability, implement their ambitious reform agenda-laid out in the National Development Strategy for 2020-30 (SND30)-and catalyze financial support from other donors.